UJI AKTIVITAS ANTIHIPERURISEMIA EKSTRAK ETANOL KULIT BUAH SUKUN (Artocarpus altilis (Parkinson) Fosberg) PADA MENCIT PUTIH JANTAN GALUR SWISS WEBSTER - Renggana, Hesti; Sujana, Dani; Martiani, Isye; Amalia, Nur; Rantika, Nopi; Hindun, Siti; Rachyani, Evitri Risa (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Hyperuricemia is defined as an elevated serum uric acid level beyond the normal physiological range, which may result from increased purine metabolism or impaired renal excretion of uric acid. Long-term pharmacological management of hyperuricemia can lead to adverse effects, highlighting the need for alternative treatments derived from natural sources. One such alternative is the skin of Artocarpus altilis, which is rich in flavonoids. The objective of this study was to evaluate the antihyperuricemic activity of ethanol extract from Artocarpus altilis fruit skin in male mice induced with potassium oxonate and chicken liver extract. Serum uric acid levels were quantified using the Point of Care Testing (POCT) method with an Easy Touch® digital device. The doses administered were 100, 200, and 400 mg/kgBW, with 13 mg/BW of Allopurinol as a positive control. Statistical analysis was conducted using ANOVA followed by post-hoc LSD tests. The results indicated that the ethanol extract of breadfruit skin exhibited significant antihyperuricemic activity at all tested doses. A dose of 100 mg/kgBW resulted in a 40.72% reduction in serum uric acid levels, with an efficacy of 68.33%. The observed effect is likely attributed to the flavonoid content, which inhibits xanthine oxidase, thereby making the 100 mg/kgBW dose the most effective in reducing uric acid levels.